Cultural Foundation of Catholic-Muslim Dialogue in Manggarai, Flores-Indonesia - Herlina Hadia (Ledalero Institute of Philosophy and Creative Technology (IFTK Ledalero), Indonesia, 2026)
This paper explores the cultural contributions to dialogue between Catholic and Muslim communities in Manggarai, Flores–Indonesia. While interreligious dialogue in Indonesia often focuses on theological and doctrinal commonalities, this study proposes a more contextual approach by examining the role of cultural traditions in building peaceful coexistence. Using qualitative research methods through purposive sampling and in-depth interviews with nine participants—consisting of religious and cultural leaders, community figures, and government representatives—the study reveals how cultural practices such as lejong (encounter), dodo (mutual cooperation), and the inclusive character of Manggarai society strengthen interreligious relations. The research also identifies several challenges in developing dialogue, including a lack of mutual understanding, the influence of extreme external views, and the politicization of religion. Nevertheless, the findings show that deeply rooted cultural values in Manggarai society provide a strong foundation for fostering dialogue, mutual respect, and cooperation between Catholics and Muslims. By emphasizing lived experience and cultural expression, this study offers a model of interreligious dialogue grounded in local context that can be applied in other pluralistic societies.